2015
DOI: 10.1093/gbe/evv042
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Metazoan Mitochondrial Replicase

Abstract: The large number of complete mitochondrial DNA (mtDNA) sequences available for metazoan species makes it a good system for studying genome diversity, although little is known about the mechanisms that promote and/or are correlated with the evolution of this organellar genome. By investigating the molecular evolutionary history of the catalytic and accessory subunits of the mtDNA polymerase, pol γ, we sought to develop mechanistic insight into its function that might impact genome structure by exploring the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 81 publications
0
30
0
Order By: Relevance
“…Furthermore, it has been demonstrated that the dimeric accessory subunit of HsPol ␥ (Pol ␥␤) enhances the ssDNA binding affinity of Pol ␥␣ by ϳ100-fold and increases its processivity by 50 -100-fold (31,39). Given that the insect Pol ␥ contains a monomeric Pol ␥␤, the differences we observe in their interactions with the template DNA may also reflect differences in the contributions of Pol ␥␤ to the properties of the holoenzyme (17). In that regard, it has been demonstrated that mutations within the dimerization interface of human Pol ␥␤, which is absent in the insect homologue, result in decreased formation of a productive Pol ␥-DNA complex, resulting in a lower processivity of the enzyme (17,40).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, it has been demonstrated that the dimeric accessory subunit of HsPol ␥ (Pol ␥␤) enhances the ssDNA binding affinity of Pol ␥␣ by ϳ100-fold and increases its processivity by 50 -100-fold (31,39). Given that the insect Pol ␥ contains a monomeric Pol ␥␤, the differences we observe in their interactions with the template DNA may also reflect differences in the contributions of Pol ␥␤ to the properties of the holoenzyme (17). In that regard, it has been demonstrated that mutations within the dimerization interface of human Pol ␥␤, which is absent in the insect homologue, result in decreased formation of a productive Pol ␥-DNA complex, resulting in a lower processivity of the enzyme (17,40).…”
Section: Discussionmentioning
confidence: 89%
“…Given that the insect Pol ␥ contains a monomeric Pol ␥␤, the differences we observe in their interactions with the template DNA may also reflect differences in the contributions of Pol ␥␤ to the properties of the holoenzyme (17). In that regard, it has been demonstrated that mutations within the dimerization interface of human Pol ␥␤, which is absent in the insect homologue, result in decreased formation of a productive Pol ␥-DNA complex, resulting in a lower processivity of the enzyme (17,40). Different properties of the D. melanogaster and H. sapiens polymerases ␥ might also be extrapolated to the mtDNA replication process to suggest that although the overall efficiency of DNA synthesis in both systems is probably similar, the mechanism of initiation of DNA strand synthesis may differ.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The heterotrimeric organization of the human replicase, comprising a single Pol γ-α and two Pol γ-β polypeptides, appears to be common to all vertebrate mtDNA polymerases [18]. Pol γ-α consists of three domains, arranged spatially to interact with the Pol γ-β dimer, and to facilitate the transition between its 5′-3′ polymerase and 3′-5′ exonuclease activities (Figure 2).…”
Section: Structure-function Relationships In Mtdna Replication Promentioning
confidence: 99%